Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.indcrop.2019.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable thermal insulation biocomposites from rice husk, wheat husk, wood fibers and textile waste fibers: Elaboration and performances evaluation

Abstract: Building materials derived from agricultural and industrial waste are becoming more attractive in the civil engineering and architectural applications because of their sustainability and lower environmental impact. In addition, substantial value can be added to the wastes by producing value added products from them. Therefore, four different types of locally available by-products (rice husk, wheat husk, wood fibers and textile waste fibers) were used to produce composites with a biodegradable poly(butylene adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(111 citation statements)
references
References 54 publications
5
101
0
5
Order By: Relevance
“…Many other research works confirmed that the use of discarded products of industrial and agricultural processes can be used as based materials for insulating panels. In [10] locally available by-products (rice husk, wheat husk, wood fibre, and textile waste fibre) were used to produce composites with a biodegradable poly(butylene adipateco-terephthalate)/poly(lactic acid) (PBAT/PLA) blend binder by hot pressing. The density and thermal conductivity of the produced composites were in the 378-488 kg/m 3 and 0.08-0.14 W/mK range, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many other research works confirmed that the use of discarded products of industrial and agricultural processes can be used as based materials for insulating panels. In [10] locally available by-products (rice husk, wheat husk, wood fibre, and textile waste fibre) were used to produce composites with a biodegradable poly(butylene adipateco-terephthalate)/poly(lactic acid) (PBAT/PLA) blend binder by hot pressing. The density and thermal conductivity of the produced composites were in the 378-488 kg/m 3 and 0.08-0.14 W/mK range, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the wheat fibre chaff showed excellent thermal conductivity coefficient under steady-state and dynamic conditions (0.307 W m −1 K −1 and 0.298 W m −1 K −1 , respectively) [141]. Several research also established the good thermal resistance of straw fibres BCB [127,[142][143][144][145][146]. Therefore, straw fibres BCB have good thermal insulation effect, which could be mainly used as filling materials in the refrigerator, chemical transportation pipeline insulation material, and thermal insulation layer of building wall surface etc just like in the case of rigid polyurethane foams manufactured from corn straw powder [147].…”
Section: Fibre Typementioning
confidence: 95%
“…Anti-odour, antimicrobial, aromatic; UV radiation protection [34,35] Rice husks Rice processing Thermal insulation potential [36] Eucalyptus bark Wood processing industry Antimicrobial, aromatic [37,38] Pine bark To feed Antioxidant, antimicrobial, aromatic [39,40] Pine sawdust, composite sawdust, powder and pieces…”
Section: Coffee Grounds Coffee Production Processmentioning
confidence: 99%